Possible protective effect of milk, meat and fish for cerebrovascular disease mortality in Japan. - Kinjo, Y; Beral, V; Akiba, S; Key, T; Mizuno, S; Appleby, P; Yamaguchi, N; Watanabe, S; Doll, R (1999)
Cerebrovascular disease was a leading cause of death from 1955 to 1980 in Japan. The mortality rate from this disease has decreased sharply in recent decades. This downward trend seems to correspond to the dietary habits of Japanese. Data from a large prospective cohort study were analyzed to examine the association between dietary habits and cerebrovascular disease mortality in Japan. The subjects for this analysis were 223,170 men and women aged 40 to 69 at baseline in December 1965. There were 6,168 deaths in men and 4,862 deaths in women due to cerebrovascular disease (ICD7: 330-334) during the follow-up period from January 1966 to December 1981. Rate ratio (RR) and 95% confidence interval (95% CI) adjusted for sex, attained age, follow-up period, prefecture, cigarette smoking, alcohol drinking and occupation was used for comparison. In this study, the risk of mortality from cerebrovascular disease was inversely associated with dairy milk, meat and fish consumption. Therefore the joint effect of dairy milk, meat and fish (DMF) as animal fat and protein was of interest. In the binary analysis, DMF (D, M, F) means the combination of dairy milk (1-3 times/week or more), meat (1-3 times/week or more) and fish (4 times/week or more). Thus DMF (d, m, f) was the reference group having dairy milk (less than 1 time/week), meat (less than 1 time/week) and fish (less than 4 times/week). For the disease, the RR of DMF (D, M, F) was 0.68 with 95% CI of 0.63 to 0.74, relative to the reference group. Furthermore the joint effect of DMF was more strongly associated with cerebral haemorrhage (ICD7: 331, DMF (D, M, F); RR: 0.63, 95% CI: 0.55-0.70) than with cerebral embolism and thrombosis (ICD7: 332, DMF (D, M, F); RR: 0.79, 95% CI: 0.70-0.89). These findings suggest that the increasing intake of animal fat and/or protein may have played a key role in reducing cerebrovascular disease in Japan.